The Effect of Pressure on Pellet Formation of Polycrystaline Superconductors Ybco Versus Ybcago. - Bidarian, Abe (1999)
Keywords: dept.phy; faculty_collection; sabbatical_report

Laboratory Research in Spectral Attenuation in Optical Fibers. - Dolan, James (1995)
Keywords: dept.phy; faculty_collection; sabbatical_report

[ Development of a Device That Would Continuously Monitor Build-up of Fluid in the Lungs ] - Wolf, Elizabeth (1990)
Keywords: dept.phy; faculty_collection; sabbatical_report

Corridor displays in glass cabinets - Matthews, L.D. (American Journal of Physics, 1976)
Keywords: dept.phy

Total Reflection in a Moving Medium - Porter, W.S. (American Journal of Physics, 1972)
Keywords: dept.phy

Improving the Small Hole Air Track and Table - Chonacky, N.J.; Snyder, J.W.; Matthews, L.D. (American Journal of Physics, 1971)
Keywords: dept.phy

Microcomputer data management in an introductory physics laboratory - Chonacky, N. (American Journal of Physics, 1982)
A microcomputer/mini-floppy disk system is used by students in the laboratory portion of an introductory physics course for science majors. Its purposes are to store their experimental data, do data analyses, and exchange messages with the lab instructor. The system also provides computer-assisted instruction (CAI) simulations of certain lab experiments, and interfaces with measuring equipment in certain experiments. Each student has a personal diskette for data files and basic utility programs for an entire semester. The ease of disk data manipulation under program control is exploited in the following ways: (i) a wide variety of data reduction techniques are introduced that permit quantitative comparisons between experimental results and theoretical expectations; (ii) facile data reduction and analyses permit preliminary processing of experimental data during the course of the lab period, so that decisions can be made by students concerning the course of the remainder of the experiment; (iii) accumulated data from various experiments become a course database permitting subsequent analyses of old data adapted in several different logical ways (e.g., RC curcuit data first treated as energy storage, later as one of a number of exponential relationships); (iv) comprehensive course database formed by merging regarding the reliability of experiments. These considerations favor laboratory goals different from the demonstration and confirmation of given physical laws. Specifically they inculcate critical thinking and hypothetico-deductive reasoning. I discuss several very real problem areas that plagued this novice and compromised implementation. I compare these problems with the qualitative improvements in laboratory learning. © 1982, American Association of Physics Teachers. All rights reserved.
Keywords: dept.phy

A video technique for the quantitative analysis of the Poisson spot and other diffraction patterns - Wein, G.R. (American Journal of Physics, 1999)
A new approach is presented for the observation and analysis of diffraction phenomena. Using the discussed procedures, direct comparison between measured light intensity and theoretical predictions is possible. A modified version of a Poisson spot experiment where the resulting diffraction pattern is recorded by a Sanyo vidicon camera is presented. A double slit experiment is also discussed, demonstrating the quantitative possibilities while addressing detector linearity. A video signal is connected directly to a computer and analyzed using public domain software. This is an excellent arrangement for demonstrations, student labs, or a more general diffraction experiment. © 1999 American Association of Physics Teachers.
Keywords: dept.phy

Ultra-violet argon dayglow lines in the atmosphere of mercury - Zeelik, Michael; Dalgarno, Alexander (Planetary and Space Science, 1973)
We investigate the response of an atmosphere of argon to solar ultra-violet radiation. With the assumption that Mercury has an argon atmosphere that is optically thick to ionizing radiation the intensities of the ultra-violet dayglow lines resulting from photoelectron impact are calculated. For most of the model atmospheres, the predicted intensities are above the detection threshold of the 1973 Venus-Mercury ultra-violet spectrometer of Broadfoot, McElroy and Belton. © 1973.
Keywords: dept.phy

A technique for measuring the 3-dimensional to 2-dimensional conductivity change of YBCO superconductors at the normal-to-superconducting phase change - Hmurcik, Lawrence V; Bidarian, A; Ibarra, B; Matthews, L D (Journal of Materials Science, 1998)
It is well known that conduction in YBa2Cu3O7 (YBCO) is by means of copper "planes" and "chains," where planes and chains describe the degree of bonding between copper and oxygen. Changes of conductivity versus temperature have been used to show that conduction in YBCO in the normal state is 3-dimensional, while conduction approaching the onset of the superconducting state is first 2-dimensional and then 3-dimensional. We have found another method to monitor this 2-to-3 transition. Using square samples, and measuring the voltage at each corner caused by a current applied to the opposite corners, one can find the conductivities along the x-axis and the y-axis. The ratio of these conductivities is unity for homogeneous samples in the normal state. However, in transition to the superconducting state, the ratio of conductivities changes. We examine this change as a function of sample purity, sample history, and exposure to an external magnetic field. Our data are consistent with data reported in the literature, and they suggest the existence of another state change deep in the superconducting state, which is only observable with the application of a magnetic field., Measurements were also carried out to correlate the anisotropy with sample porosity. Measurements of normal state resistivity, critical temperature, and critical current characterize the sample's porosity, and these data affect the anisotropy in the superconducting state in a manner directly proportional to the porosity., (C)1998 Kluwer Academic Publishers
Keywords: Anisotropy; Critical temperature; Electric conductivity measurement; Electric current measurement; High temperature superconductors; Magnetic field effects; Oxide superconductors; Phase transitions; Porosity; Temperature measurement; Voltage measurement; Yttrium barium copper oxides; dept.phy